Single-Cell Transcriptional Profiling Reveals Sex and Age Diversity of Gene Expression in Mouse Endothelial Cells - Huang, Xianxi; Shen, Wenjun; Veizades, Stefan; Liang, Grace; Sayed, Nazish; Nguyen, Patricia K. (Frontiers in Genetics, 2021)
Although it is well-known that sex and age are important factors regulating endothelial cell (EC) function, the impact of sex and age dimorphism on the gene expression of ECs has not been systematically analyzed at the single cell level. In this study, we performed an integrated characterization of the EC transcriptome of five major organs (e.g., fat, heart-aorta, lung, limb muscle, and kidney) isolated from male and female C57BL/6 mice at 3 and 18 months of age. A total of 590 and 252 differentially expressed genes (DEGs) were identified between females and males in the 3 month and 18 month subgroups, respectively. Within the younger and older group, there were 177 vs. 178 DEGS in fat, 305 vs. 469 DEGs in heart/aorta, 22 vs. 37 DEGS in kidney, 26 vs. 439 DEGS in limb muscle, and 880 vs. 274 DEGS in lung. Interestingly, two transcripts -LARS2, a mitochondrial leucyl tRNA synthase, and DDX3Y, a Y-related transcript which regulates cell proliferation and apoptosis -were differentially expressed in all organs in males compared to females in the 3 month group while S100a8 and s100a9, which are calcium binding proteins that are increased in inflammatory and autoimmune states, were upregulated in all organs in males at 18 months. Gene enrichment analysis found genes enriched in protein targeting, catabolism, mitochondrial electron transport, IL 1-and IL 2-signaling, and WNT signaling in males vs. angiogenesis and chemotaxis in females at 3 months. In contrast, ECs from males and females at 18 months had up-regulation in similar pathways involved in inflammation and apoptosis. Taken together, our findings suggest that gene expression is largely similar between males and females in both age groups. Compared to younger mice, however, older mice have increased expression in genes involved in inflammation.